Impacto de fatores socioeconômicos na sobrevida de pacientes na fila de espera e após transplante cardíaco - Parra, Andrelisa Vendrami (2007)
Cardiac transplantation aims at the improvement of survival as well as quality of life of patients with end-stage Chronic Cardiac Failure. Socioeconomic status is believed to have an important role in the success of the surgical procedure. This study, therefore, aimed at identifying the impact of socioeconomic status on survival of patients listed for heart transplantation as well as in cardiac transplant recipients. A retrospective longitudinal cohort study was carried out using data obtained from the medical charts 70 patients treated in the Hospital de Base da Faculdade de Medicina de São José do Rio Preto. The socioeconomic evaluation was made through the following indicators: monthly income, education, conditions of housing, profession, profession of the family members, presence of caregiver and distance to the hospital. These data are used in the classification for defined stratus: Low Inferior (BI), Low Superior (BS), Inferior Medium (MI), Medium (M), Superior Medium (MS), High (H). Seventy-six per cent of patients on the waiting list for heart transplantation were classified in the low socioeconomic class; 77% of such patients had low educational level, 77% adequate housing, 94% a caregiver, 59% no social insurance after retirement, and 60% received financial support from other nongovernmental entities. Forty-four per cent of patients had a positive serology for Chagas disease. Probability of survival at 100 days of follow up in the waiting list was 68% for Chagas disease and 79% for non-Chagas disease patients (p>0,05). With regard to cardiac transplant recipients, 84% of them were classified in the low socioeconomic class, 73% had low educational level, 75% adequate housing, 93% caregiver, 57% no social insurance after retirement, and 32% had financial support from other nongovernmental entities. Thirty-two cardiac transplant recipients had a positive serology for Chagas disease. Survival probability at 100 days of follow up for cardiac transplant recipients was 62% for Chagas disease and 81% for non-Chagas disease patients (p>0,05). The data obtained in this work demonstrate that socioeconomic status not only has no impact on patients on the waiting list for heart transplantation, but also on outcome of cardiac transplant recipients because patients in the low socioeconomic status had a similar prognosis than patients in the median socioeconomic class. Thus, socioeconomic status has no unfavorable prognosis for both patients on the waiting list as well as for cardiac transplant recipients.